Collaborative Approach on Digital Government Transformation in West Java. - Maulana, Rio Yusri; Anry Firmansyah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
The world is witnessing exponential growth and rapid change brought about by the advent of the digitalisation era. This change offers an opportunity to revisit the strategic approach on using Information and Communication Technologies (ICTs) to improve the delivery of public value. Considering that governments around the world are now facing declining levels of public trust. Using so-called digital transformation, governments adapt the wide use of ICTs to better support government functions, services, and citizens, encouraging their participation in policy-making processes. Successful government digital transformation often depends on the ability of multiple government or non-government organisations to collaborate towards shared objectives. However, most governments are far from fully exploiting the benefits of ICTs, and often forget that in some social groups, access to ICTs is limited at the point of digital inequality. This article provides an overview of how the Indonesian local government implements its digital-based policy, which is centered on an electronic-based government system in Indonesia (SPBE), linking cross-sectoral central government agencies. In recent years, government organisations have spent a large part of their budgets on information and communication systems and rely on these systems for their functioning. However, the complexity of the digital transformation still requires considerable effort, especially when it comes to a lack of ICT infrastructure, human resources, and bureaucratic culture. By using qualitative methods, knowledge is formed through the perspective and way of interpretation that comes from the participants included in the research, not limited to the research implementer. The data will be collected through literature study, in-depth interviews, and observations. The aim of the research is to describe how collaborative governance contributes to the policy process of using ICTs to deliver inclusive policies by local governments.